Pengaruh Abdullah Sani Sebagai Kandidat Wakil Gubernur dalam Meraih Suara Masyarakat Muslim pada Pilkada Provinsi Jambi Tahun 2020 - Ahmad, Zakly Hanafi; Anshori, Muhammad Wira; Pratama, Galank (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
Jambi gubernatorial election in 2020 reaped many dynamics and a long process until it ended in the Constitutional Court. One of the interesting things in this dynamic process is the involvement of religious issues, especially the role of ulama and Islamic organizations in the victory of the Al Haris and Abdullah Sani pair. The movement of religious issues is inseparable from the figure of Abdullah Sani, who is known as a scholar and has a strong influence among Nahdliyin. The purpose of this study is to see how the influence of Abdullah Sani as a candidate for Deputy Governor in gaining the votes of the Muslim community in the 2020 Jambi Governor election. The method used in this study is qualitative with a literature study approach. The results of this study indicate that Abdullah Sani's decision to run as Al Haris' companion in the 2020 Jambi Governor election was the right decision, Abdullah Sani's track record and contribution in the religious field as well as the clerical charisma inherent in him succeeded in attracting the sympathy of the Muslim community of Jambi Province, a declaration of support From the ulama and Islamic organizations there was also a lot of flow, even after the re-voting this pair was declared victorious and succeeded in sitting as Governor and Deputy Governor of Jambi.